The Elements - Penrose, Jim; Johnson, Gordon P.; Leyden, Michael B. (Addison-Wesley video lessons, 1988)
Summary: Discusses the periodic table, demonstrates the differences between metals, non-metals and metalloids and illustrates uses and properties of the commonest elements.